Risk Management and Performance of Conventional Banks in Pakistan - ALAM REHMAN; YASIR KHAN; ARIF HUSSAIN (Journal of Business & Tourism, 2021)
The study examines the relationship between risk management and performance of conventional banks in Pakistan. The study has been conducted using Capital adequacy ratio, non-performing loan ratio, Cost per loan ratio, Cash reserve ratio and Z-scoring ratio as the proxies of risk management and Return on asset has been used as the proxy of the bank financial performance. The study has used random sampling technique for the 20 conventional banks for the period 2010 to 2016. The study uses correlation and simple OLS to test the hypothesis. The results reveal that capital adequacy ratio and Z-scoring have positive significant impact on the conventional banks, financial performance, where as Non-performing ratio, cost per loan ratio and cash reserve ratio predicting negative affect on the financial performance of the conventional banks in Pakistan. The study has practical as well as theoretical implications. The results are expected to help policy makers to rehash their policies by encompassing the approaches that facilitate the risk management of banks in Pakistan. The study will also help researchers in strengthening their level of understanding of these relationships. Replication of the study may help to validate the hypothesized model and their consequent application in the organizations that share somewhat similar organizational structures.